Inclusive Education Policy In Indonesia: Best Practices, Challenges, And Future Directions - Nabiela, Himmaya Syahnas; Ulfatin, Nurul (International Journal of Educational Research & Social Sciences, 2023)
Inclusive education in Indonesia aims to provide equal access to education for all children, including those with special needs. The government's adoption of inclusive policies aims to create a discriminatory-free educational environment. Best practices involve developing a curriculum that supports diversity, providing teacher training to enhance their understanding of the needs of special students, and fostering an inclusive school environment. Despite challenges such as a lack of resources and social stigma, collaboration among schools, parents, and communities is considered crucial for success. Overcoming these challenges requires further efforts. The future direction of inclusive education policies includes teacher training, improving the accessibility of educational facilities for students with special needs, and expanding collaborations with relevant stakeholders. Policy updates and responsive educational programs are key to creating a sustainable inclusive education system in the future.